Translating politeness cues in Philippine missionary linguistics: "Hail, Mister Mary!" and other stories. (2nd January 2016) - Sales, Marlon James
Abstract : The earliest and most extensive systematic descriptions of Philippine languages are found in the grammatical and lexicographical works of Spanish Catholic priests from the seventeenth to the nineteenth centuries. Tagalog was the most studied among these languages, and was generally portrayed as the most "refined" because of certain cues that overtly mark verbal politeness. As these politeness cues were taken as translation constraints in Latinate tongues, they are often explained through solutions that operated on arbitrary equivalences between Tagalog and Castilian. A closer reading of these equivalences reveals that aside from the reduction of language to the usual categories of grammar, the proposed translation solutions also inscribed verbal politeness within a hierarchized vision of colonial polity, and repurposed the pre-existing mechanisms of Tagalog so as to articulate a Christian(ized) discourse.